Effect of 5-Aminolevulinic Acid Photodynamic Therapy on Aspergillus fumigatus Biofilms in Vitro - Zhimin Duan; Jianbo Tong; Nana Zheng; Rong Zeng; Yuzhen Liu; Min Li (Current Microbiology, 2023)
Aspergillus fumigatus biofilm development results in enhanced pathogenicity and treatment resistance. Most contemporary antibiotics, however, are unable to eliminate biofilms. In recent years, with the application of new photosensitizers and the development of treatment, ALA-PDT (5-aminolevulinic acid photodynamic treatment) has achieved remarkable curative effect in the treatment of fungal infectious diseases; however, no research has been conducted on ALA-PDT against A. fumigatus . This study investigated the inhibitory effect of ALA-PDT at various 5-aminolevulinic acid concentrations and light doses on A. fumigatus planktonic and biofilms in vitro. We found that ALA-PDT may successfully inhibit the development of A. fumigatus biofilm and disintegrate mature biofilm. After ALA-PDT treatment, the adherence rate and vitality dramatically decreased, and the biofilm’s structure was severely compromised. Our findings show for the first time that ALA-PDT may be used to prevent the formation of A. fumigatus biofilm and disturb the structure of mature biofilm, and that it could be employed as a therapeutic therapy for A. fumigatus superficial infection.

Colonization Characteristics of Poplar Fungal Disease Biocontrol Bacteria N6-34 and the Inhibitory Effect on Pathogenic Fungi by Real-Time Fluorescence Quantitative PCR Detection - Rong-bo Sa; Jun-li Zhang; Ji-zheng Sun; Yan-xia Gao (Current Microbiology, 2021)

Marinobacter shengliensis subsp. alexandrii Subsp. Nov., Isolated from Cultivable Phycosphere Microbiota of Highly Toxic Dinoflagellate Alexandrium catenella LZT09 and Description of Marinobacter shengliensis Subsp. shengliensis Subsp. Nov - Xi Yang; Rong Xiang; Nurhezreen Md Iqbal; Yu-Han Duan; Xiao-Ai Zhang; Lei Wang; Lin-Zeng Yu; Jia-Zhou Li; Ming-Fei Sun; Qiao Yang; Chun-Tian Zheng; Shen-Quan Liao (Current Microbiology, 2021)

Halovenus rubra sp. nov., Isolated from Salted Brown Alga Laminaria - Dong Han; Wen-Jiao Zhang; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2015)

Halobellus litoreus sp. nov., a Halophilic Archaeon Isolated from a Chinese Marine Solar Saltern - Mei-Lin Zhao; Xing-Xing Qiu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2014)

Changes of Curdlan Biosynthesis and Nitrogenous Compounds Utilization Characterized in ntrC Mutant of Agrobacterium sp. ATCC 31749 - Li-Jun Yu; Jian-Rong Wu; Zhi-Yong Zheng; Xiao-Bei Zhan; Chi Chung Lin (Current Microbiology, 2011)